Meningkatkan Pemahaman Konsep Bilangan melalui Media Kartu Angka di MI Cut Nyak Dien - Waroah, Siti; Rofiqoh, Rofiqoh; Rusmila, Rusmila (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve students' understanding of numerical concepts at MI Cut Nyak Dien through the use of number card media. The main issue in mathematics learning is students' low ability to recognize, compare, and systematically operate numbers. This study was conducted in two cycles, each consisting of planning, action implementation, observation, and reflection. The research subjects were lower-grade students who had difficulty understanding numerical concepts. Data were collected through tests, observations, and teacher interviews. The findings indicate that the use of number card media gradually improved students' comprehension of numerical concepts. In the first cycle, there was an improvement in number recognition and understanding relationships between numbers, although some students still struggled with basic operations. In the second cycle, more significant progress was observed, with students gaining confidence in performing basic arithmetic operations and actively engaging in learning. Supporting factors for this success included the use of engaging media and active student participation in learning activities. However, challenges such as time constraints and varying levels of student understanding were encountered. Therefore, integrating number card media with other teaching methods should be considered to achieve optimal learning outcomes. These findings are expected to serve as a reference for teachers in developing innovative mathematics teaching strategies in madrasah settings.